Analysis of Battery Management Algorithms on DC Microgrids - Nugroho, Vendi Ardianto; Wardana, Awang Noor Indra; Suroso, Dwi Joko (ELKHA : Jurnal Teknik Elektro, 2021)
Management of battery at direct current (DC) microgrids is the essential factor to maintain the balance of power and the bus voltage's stability in the grids. To ensure the quality of battery management is necessary to simulate the operation of the battery management system. This paper presents the simulations in various battery management algorithms.   The simulations were designed to determine the effect of these variations on the balance of the power balance, bus voltage stability, and battery consumption level. The configurations of one, two, and three battery groups could maintain a balance of power balance. The three arrangements could ensure the bus voltage stability at a value of 24 Volts. The variations in the battery group configurations cause different battery consumption levels. The three-battery group configuration has a lower power consumption rate of 0.1% than other battery group configurations. Variations in the battery management algorithms affect power balance, bus voltage stability, and battery electricity consumption.   The result showed the best power balance achieved by an algorithm without counting a value-based state of charge (SoC). The algorithm also committed that the difference between the supply and demand equal to 0 Watts.   For the voltage stability, the algorithms that were counting a value-based SoC can maintain bus voltage stability at a value of 24 Volts.   Nevertheless, other algorithms that rely on less than one SoC value-based and have the lowest mean value of SoC reduction are equal to 0.19%.